What Hangs On a Hairpin: Inalienable Possession and Language Exchange in Two Marriage Romances. (3rd July 2021) - Wang, Yuanfei
Abstract : This paper discusses the figuration of the purple jade hairpin as inalienable possession in the Tang author Jiang Fang's (792–835) marriage romance "Huo Xiaoyu's story" and the Ming playwright Tang Xianzu's (1550–1616) dramatic adaptation of the story, The Purple Hairpins (1595). Examining how the hairpin's materiality and symbolism intersects with the tradition of classical poetry and marriage laws, the paper shows opposing poetics — the critical and the lyrical — of the two marriage romances. Whereas the selling of the hairpin in the Tang romance indicates the loss of Huo Xiaoyu's identity and the culture of romance — a true social order of exogamy based upon language exchange — the circulation of her hairpins in The Purple Hairpins authenticates her identity and the culture of romance.